Progressive exacerbation of neurological symptoms in a patient with neurosyphilis following T9-T10 intradural space-occupying lesion resection: a case report - Meng, Yongpeng; Bo, Yan; Wei, Hongtao (Frontiers in Immunology, 2026)
BackgroundNeurosyphilis is a disease of the central nervous system (CNS) caused by Treponema pallidum (syphilis spirochete), which usually presents with a variety of nonspecific symptoms and is easily misdiagnosed. Although Treponema pallidum can remain latent after treatment, reactivation may occur in the presence of a compromised or immunosuppressed immune system. This article reports a case of reactivation of neurosyphilis after spinal surgery, with the aim of exploring the possible role of immunosuppression in the process.Case presentationThe patient was a 75-year-old female admitted to the hospital with persistent bilateral lower extremity pain and weakness and a past history of syphilis that was cured 31 years ago. Upon admission, the patient was diagnosed with an intradural occupying lesion and underwent T9-T10 intradural space-occupying lesion resection. Postoperatively, the patient developed symptoms of neurogenic bladder and paraplegia, and further examination revealed abnormal cerebrospinal fluid suggestive of reactivation of neurosyphilis. Through syphilis antibody testing and cerebrospinal fluid analysis, the diagnosis of neurosyphilis was finally confirmed and antisyphilis treatment was started.Treatment and outcomeThe patient received a 14-day course of intravenous benzylpenicillin, which resulted in significant symptomatic improvement and restoration of most functions at discharge. After 12 months of follow-up, the patient had fully recovered, with a progressive decrease in syphilis antibody titers and no neurosyphilis reactivation.ConclusionsThis case emphasizes the importance of preoperative syphilis antibody screening, especially in elderly patients with a history of syphilis. The immunosuppressed state may contribute to the reactivation of syphilis spirochetes; therefore, it is important to consider this potential risk and take appropriate precautions when performing surgical treatments such as spinal surgery. Penicillin remains the therapeutic agent of choice for neurosyphilis, and early diagnosis and treatment are critical to the patient’s prognosis.